LncRNA XIST upregulates TRIM25 via negatively regulating miR-192 in hepatitis B virus-related hepatocellular carcinoma - Jiancheng Wang; Gang Yin; Hu Bian; Jiangli Yang; Pengcheng Zhou; Kai Yan; Cheng Liu; Pei Chen; Jun Zhu; Zhi Li; Tongqing Xue (BMC, 2021)
Abstract Background Long non-coding RNA (lncRNA) XIST has been implicated in the progression of a variety of tumor diseases. The purpose of this study was to explore the molecular role of lncRNA XIST in human hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). Methods The expression levels of lncRNA XIST, miR-192 and TRIM25 in HBV-related HCC tissues and HepG2.2.15 cells were detected by qRT-PCR. Biological information and luciferin gene reporter assay were performed to detect the interaction among lncRNA XIST, miR-192 and TRIM25. CCk-8 assay, wound healing assay and colony formation assay were conducted to detect the proliferation and migration ability of HepG2.2.15 cells. Results qRT-PCR results showed that the expression levels of lncRNA XIST were remarkably increased in HBV-related HCC tissues and HepG2.2.15 cells. In addition, miR-192 was a direct target gene of lncRNA XIST, and the expression of miR-192 and lncRNA XIST were negatively correlated. Moreover, overexpression of miR-192 observably inhibited the proliferation and migration of HCC cells, while overexpression of lncRNA XIST showed an opposite effect. Furthermore, TRIM25 was a direct target of miR-192, and lncRNA XIST could up-regulate the expression of TRIM25 by targeting miR-192. Conclusion LncRNA XIST could up-regulate the expression of TRIM25 by targeting and binding to miR-192, thus accelerating the occurrence and development of HCC.